2018
DOI: 10.1101/388280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A speech envelope landmark for syllable encoding in human superior temporal gyrus

Abstract: Listeners use the slow amplitude modulations of speech, known as the envelope, to segment continuous speech into syllables. However, the underlying neural computations are heavily debated. We used high-density intracranial cortical recordings while participants listened to natural and synthesized control speech stimuli to determine how the envelope is represented in the human superior temporal gyrus (STG), a critical auditory brain area for speech processing.We found that the STG does not encode the instantane… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 58 publications
11
62
2
Order By: Relevance
“…Conversely, it was shown that portions of STG encode the amplitude variations of speech as well as amplitudemodulated tone stimuli independent from other spectro-temporal features (Oganian and Chang, 2019). Taken together, these results reveal that in the superior temporal cortex, regions coding speech-specific spectrotemporal features and non-speech-specific envelope variations coexist.…”
Section: Martinelli Et Al 16mentioning
confidence: 78%
See 2 more Smart Citations
“…Conversely, it was shown that portions of STG encode the amplitude variations of speech as well as amplitudemodulated tone stimuli independent from other spectro-temporal features (Oganian and Chang, 2019). Taken together, these results reveal that in the superior temporal cortex, regions coding speech-specific spectrotemporal features and non-speech-specific envelope variations coexist.…”
Section: Martinelli Et Al 16mentioning
confidence: 78%
“…Do High and Low frequency ranges share a common spatial organization in the left hemisphere across linguistic materials? Previous results showed that the sound envelope is represented in speech-related cortical areas within the left hemisphere (Giraud, 2000;Oganian and Chang, 2019). An antero-posterior gradient from low to high modulation frequencies emerged (DeWitt and Rauschecker, 2012;Hullett et al, 2016).…”
Section: Envelope Amplitude Modulation Across Frequencies and Categoriesmentioning
confidence: 92%
See 1 more Smart Citation
“…We build upon recent intracranial electrocorticography (ECoG) recordings that showed that local 8 neural populations on the superior temporal gyrus (STG) selectively respond to acoustic edges in the 9 speech envelope and that envelope tracking by broadband high gamma amplitude was explained by 10 transient power increases following acoustic edges (Oganian & Chang, 2019). Results from this study 11 suggested that onset edges may be the primary acoustic feature driving speech envelope encoding.…”
mentioning
confidence: 98%
“…Another possibility is that the performance boost of the articulatory features is instead attributable to their correlation with a low-dimensional and less rich acoustic feature. It has repeatedly been observed that neuronal responses from bilateral superior temporal regions are especially sensitive to acoustic edges (Prendergast et al, 2010;Hertrich et al, 2012;Gross et al, 2013;Doelling et al, 2014;Oganian & Chang, 2018). Corresponding feature spaces extracting these onsets from envelope representations by means of half-wave rectifying the temporal gradient have previously been used by several labs (Hertrich et al, 2012;Hambrook & Tata, 2014;Fiedler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%